CLINICAL FEATURES OF OTORHINOLARYNGOLOGICAL PATHOLOGY IN CHRONIC KIDNEY - D. M. Nabieva; N. E. Makhkamova (Journals Park Publishing, 2026)
This scientific article presents a review of current knowledge on chronic kidney pathology, in particular chronic kidney failure, in both the pre- and post-transplantation periods, as well as pathological changes affecting the organs of the ear, nose, and throat.
Keywords: Chronic kidney disease, kidney transplant recipient, otorhinolaryngological complications, sensorineural hearing loss, otoacoustic emissions, short-latency auditory evoked potentials.